Assessment of pancreatic ductal stone density on non-contrast computed tomography for predicting the outcome of extracorporeal shock wave lithotripsy - Dalal, Ankit; Kamat, Nagesh; Maydeo, Amit; Patil, Gaurav; Vadgaonkar, Amol; Parekh, Sanil; Vora, Sehajad (Endoscopy International Open, 2024)
Background and study aims The utility of stone density at non-contrast computed tomography (NCCT) for predicting the effectiveness of extracorporeal shock wave lithotripsy (ESWL) in chronic calcific pancreatitis (CCP) is relatively unexplored.Patients and methods This was a prospective observational study of patients with CCP. Hounsfield units (HU) were determined for the largest pancreatic ductal stone during pretreatment NCCT. All patients underwent ESWL until the largest stone was fragmented to <3mm, followed by endoscopic retrograde cholangiopancreatography (ERCP) for stone extraction. The predictive factors following ESWL for successful stone extraction were studied and the receiver operating characteristic (ROC) curve determined the HU optimal cut-point.Results Eighty-two patients with a median (interquartile range) age of 36 years (range, 29–55); majority male 45 (54.9%), were included. Idiopathic CCP was noted in 78 patients (95.1%). The median stone density (SD) was 1095 HU (range, 860.7–1260.7) and the number of ESWL sessions was 2 (range, 2–3). Complete stone removal at index ERCP was achieved in 55 patients (67.1%). Those with partial clearance (n=27) needed a repeat ERCP, which was successful in 26 (96.3%); one patient (3.7%) underwent surgery. There was a significant, positive correlation between number of ESWL sessions and SD (r=0.797; P<0.001). On bivariate analysis, SD and the number of ESWL sessions revealed a significant association with complete ductal clearance. The optimal cut-point for complete stone removal by the ROC curve was 1106.5 HU (Youden index 0.726), with a sensitivity of 93% and a specificity of 80%.Conclusions The SD is a significant predictor of ESWL success followed by ductal clearance at ERCP, and <1106.5 HU is a predictor of good candidates for ESWL therapy.
Keywords: Stones; Pancreatobiliary (ERCP/PTCD); Strictures